Waste-to-wealth : From printer toner waste into valuable magnetic materials - Nurul Hidayah, Ghazali; Rodziah, Nazlan; Siti Norain, Abdul Mubin (2021)
To recover magnetite (Fe2O3) by magnetic separation technique and convert into Fe2O3 using reduction technique. To synthesize Nickel Zinc Ferrite (NZF) using extracted iron oxide from waste toner powder. To study the structural, microstructural and magnetic properties of Nickel Zinc Ferrite (NZF) prepared using extracted Fe2O3 as main component.